PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) PADA MATERI ELASTISITAS BAHAN UNTUK MENINGKATKAN PROSES DAN HASIL BELAJAR SISWA DI KELAS XI IPA - Verny Sondole; Hendrich Taunaumang; Alfrits Komansilan (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2023)
This study aims to determine the effect of applying the Problem Based Learning (PBL) learning model on student learning processes and outcomes in material elasticity. The method used in this study was a pre-experimental study with a one group pretest-posttest design. This research was conducted through three stages. The first stage is to provide a pretest to measure students' initial abilities. The second stage is giving treatment through problem-based learning and the third stage is giving a posttest as a learning evaluation. The research subjects were class XI students of SMA Negeri 2 Tondano Selatan for the academic year 2022/2023. The data analysis technique used simple linear regression for the process and the results of the coefficient formula obtained showed that there was an influence of the Problem Based Learning (PBL) learning model on the learning process of students at SMA Negeri 2 Tondano with a percentage of 90.4%. Based on the significance value: from the coefficient table, a significance value of 0.000 <0.05 is obtained, so it can be concluded that variable X (Problem Based Learning model) has an effect on Y (Student Learning Process). Data analysis techniques for student learning outcomes using the N-GAIN test obtained an average pretest score of 7.0 and a posttest average score of 63.6. The results of this study indicate that the Problem Based Learning (PBL) learning model influences student learning processes and outcomes.